PERSEPSI PETANI TERHADAP PENTINGNYA PERAN PENYULUHAN PERKEBUNAN KARET (Hevea brasiliensis Muell Arg) DI KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Destika Marlina; Eri Sayamar; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this study are to figure out the implementation of extension and farmers’ perception toward the importance of the role of extension in rubber plantation in Kuantan Hulu Sub-district Kuantan Singingi Regency. The survey method was used in the research, while Random Sampling was also used as the sampling technique. The number of respondents were 49 samples. In terms of analyzing the data, Scale of Liker's Summated Rating (LSR) was used. The Result showed that, the plantation extension activities in Kuantan Hulu Sub-district have been going quite well as it can be observed upon the completeness of the extension programs and the elements of extension. The role of extension in plantation is important in the rubber farming activities with independent scheme that is observed from the education sub-variable, dissemination, facilitation, consultation, supervision, and monitoring and evaluation. Keywords: Plantation rubber. Perception farmer. Hulu Kuantan District. extension role.